A friction model having multiple factors for high-speed cutting of aluminum alloy 6061-T6. Issue 9 (June 2016) - Xu, Daochun; Feng, Pingfa; Li, Wenbin; Xu, Chao; Ma, Yuan
Abstract Tool–chip friction of high-speed cutting (HSC) is complex and involves nonlinear problems. This paper proposes a new friction model having multiple factors for HSC and investigates the multiple effects affecting the tool–chip friction coefficient. An experimental method of high-speed friction and an inverse method of obtaining the temperature of the friction interface are proposed. The proposed friction model reveals the inherent relationship between the friction coefficient and the multiple factors, and describes tool–chip friction in the HSC of aluminum alloy 6061-T6 accurately and improves the cutting simulation accuracy. It is also found that an increase in friction speed increases the friction coefficient and that an increase in friction temperature reduces the friction coefficient. However, an increase in ambient temperature clearly increases the friction coefficient at high temperature, and an increase in the normal load reduces the friction coefficient at low temperature and increases the friction coefficient at high temperature. The results provide a clear understanding of the mechanisms of friction speed and temperature, the ambient temperature, and the actual contact area in tool–chip friction of HSC.